From PD-1/PD-L1 to tertiary lymphoid structures: Paving the way for precision immunotherapy in cholangiocarcinoma treatment - Fang-Ju Huang; Ye-Ying Fang; Jia-Ying Wen; Jian-Jun Li; Qian Lin; Qin-Yan Su; Yi-Yang Chen; Lei Wang; Jian-Jia Zeng; Bang-Teng Chi; Rong-Quan He; Di-Yuan Qin; et al. (Human Vaccines & Immunotherapeutics)
Cholangiocarcinoma (CCA) is a highly malignant hepatobiliary tumor characterized by limited treatment options and poor prognosis. The recent rise of immunotherapy has significantly influenced research in this field. This study presents a bibliometric analysis of 416 articles retrieved from the WOSCC, Wan fang Data, CNKI and VIP databases, spanning contributions from 32 countries, 589 institutions and 3,200 authors. The analysis identified “PD-L1,” “PD-1” and “pembrolizumab” as central research foci, while “immune checkpoint inhibitors,” “tumor immune microenvironment,” “tertiary lymphoid structures” and “durvalumab” emerged as key areas of interest. These findings emphasize the pivotal role of immunotherapy in improving survival outcomes for CCA, and they highlight the significance of tertiary lymphoid structures within the tumor microenvironment as a promising target for future research. This study offers a strategic overview of the evolving landscape of CCA immunotherapy, providing valuable insights to guide future scientific endeavors in this domain.